2012
DOI: 10.1175/jcli-d-11-00373.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent Changes in Explosively Developing Extratropical Cyclones over the Winter Northwestern Pacific

Abstract: This study investigated recent changes in the characteristics of explosively developing extratropical cyclones over the northwestern Pacific region in winter from 1979/80 to 2010/11 by using reanalysis data from the Japanese 25-yr Reanalysis/Japan Meteorological Agency Climate Data Assimilation System (JRA-25/ JCDAS). The results showed that the frequency of explosive cyclones increased in the northwestern Pacific region east of Japan. This increase was accompanied by a decrease in the number of slowly develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…The DJF precipitation increased more rapidly in the REAL runs compared to that in the CLIM runs over the Pacific Ocean (Figure ), which suggests that the SST warming has a positive influence on the precipitation over the Pacific Ocean, and is consistent with the data analysis for the extratropical cyclone development by Iwao et al . []. Furthermore, it is interesting to note that the precipitation in CLIM runs also possesses a weak increasing trend around southeastern Japan and regions facing the Pacific Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…The DJF precipitation increased more rapidly in the REAL runs compared to that in the CLIM runs over the Pacific Ocean (Figure ), which suggests that the SST warming has a positive influence on the precipitation over the Pacific Ocean, and is consistent with the data analysis for the extratropical cyclone development by Iwao et al . []. Furthermore, it is interesting to note that the precipitation in CLIM runs also possesses a weak increasing trend around southeastern Japan and regions facing the Pacific Ocean.…”
Section: Discussionmentioning
confidence: 99%
“…The present work is an extended study of the POÁO cyclones, which is the strongest of the explosive cyclone types that occur over the NPO and shows the most drastic response to LHR (Yoshida and Asuma, 2004;Yoshiike and Kawamura, 2009;Iwao et al, 2012). The main aims are to understand the explosive development of POÁO cyclones from the PV point of view, to calculate the contributions of various factors in different layers quantitatively, to compare the relative importance of various factors during different explosive developing stages and to reveal possible interactions among different layers, especially the role of LHR.…”
Section: Introductionmentioning
confidence: 99%
“…(1) it persisted in the typical maintaining period of the POÁO cyclones (Yoshida and Asuma, 2004); (2) it moved along the major route of explosive cyclogenesis over the NPO (Iwao et al, 2012); and (3) its maximum deepening rate and minimum SLP appeared in corresponding highdensity areas (Yoshida and Asuma, 2004;Iwao et al, 2012). The cyclone was interesting because: (1) it formed around the southern boundary of the explosive-cyclone active area over the NPO and moved almost from the southern to the northern boundary of the active area (Yoshida and Asuma, 2004;Allen et al, 2010); (2) it experienced two distinct explosive developing stages, with maximum deepening rates of 1.2 and 2.6 Bergerons, respectively 1 ; and 3) the minimum central SLP was 956 hPa, implying that the cyclone was an extreme case (Kuwano- Yoshida and Asuma, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For wintertime ETCs, Iwao et al . () reported that frequency of explosive ETCs has increased over eastern Japan although total number of ETCs did not change much. Loptien et al .…”
Section: Summary and Discussionmentioning
confidence: 98%